The Role of the First 14 Amino Acids of Mature M1 Protein of Streptococcus pyogenes on Fibronectin-Binding Activity and Dimer Formation - ROGA FLORIDA KEMBAREN; ADAM REZA GANJARA; VALENTINA YURINA; DEBBIE SOEFIE RETNONINGRUM (Indonesian Society for microbiology, 2010)
Streptococcus pyogenes is one of the most important human pathogens which express a multi-facet of virulence factors on its cell surface. One of the virulence factors that has been intensively-studied is the M protein that binds several human proteins. M1 protein, a member of the M protein family, was previously found to bind human fibronectin (Fn), an activity that is responsible for bacterial internalization. A structural study showed that this protein consists of four regions: A, B, S, and C. The study was intended to investigate the role of the first 14 amino acid residues located at the non-helical region of M1 protein in binding Fn, and its ability to form a dimer. The DNA fragment encoding for the ABS protein lacking its first 14 amino acids (ABSD14aa) was cloned into pET-16b, overexpressed in Escherichia coli BL21(DE3), and the protein was purified by affinity chromatography. The purified protein was characterized by sodium dodecyl sulphate polyacrylamide gel electrophoresis and the Fn-binding activtiy was assayed by enzyme linked immunosorbent assay. The result indicated that the M1 lacking its first 14 amino acids retains its dimerization and Fn-binding activities.